Influence of material parameters on reliability indicators of two-stage thermoelectric devices - Зайков, Владимир Петрович; Мещеряков, Владимир Иванович; Журавлев, Юрий Иванович (Technology audit and production reserves, 2015)
It was taken a comparative analysis of the main parameters and reliability indicators of two-stage thermoelectric devices while using various combinations of the source materials, which differ by of thermoelectric power and electrical conductivity coefficients, for temperature changes from 60 K to 90 K and modes of operation from the maximum cooling capacity to the lowest failure rate. The possibility of reducing the total failure rate and increase the probability of failure of two-stage thermal power devices using of source materials with high electrical conductivity is presented. It was received a number of patterns which allows to determine the main parameters and reliability indices for different combinations of source materials compared with traditional modes of operation and temperature changes. Variants of combinations of averaged parameters of raw materials for the construction of two-stage thermoelectric devices including traditionally used in the production are represented. There were developed models for determination of relative distribution of thermocouples number in thermoelectric device stages, the relative failure rate model, the model of relative power consumption in stages, the model of relative cooling coefficient. The comparative analysis of the basic parameters and reliability operation indicators from the maximum cooling capacity to the lowest failure rate was taken, which has showed that compared with traditional version we get a win on the failure rate by 10-20 % with a corresponding increase in the probability of thermoelectric coolers failure-free operation. These researches can be applied in the manufacture of thermoelectric cooling devices of high reliability while maintaining the value of the product.